Literature study: Effective Training Improves Karate Punching Performance - Kadir, Suprianto (-, 2025)
Punching is one of the main basic techniques in karate that significantly determines an athlete's performance in the competition arena. Improving punching effectiveness is a crucial requirement in the training process. This study aims to identify and evaluate the most effective training methods for improving karate punching performance through a literature review of ten recent scientific articles. The method used was a systematic literature review with a qualitative descriptive approach to the results of previous research. The results indicate that resistance band training, plyometrics, and moving target training are the most consistent methods for improving punching speed, power, and accuracy. Most methods are also economical and applicable. This study demonstrates that structured and measurable physical training can be an effective strategy for improving karate athlete performance. These findings can be used as a basis for developing evidence-based training programs in educational settings and sports clubs.